Teachers’ Perception and Practices of Intercultural Communicative Competence Integration in EFL Classroom: A Systematic Literature Review - Nafisah, Shofia; Oktarina, Ika; Santri, Dewi; Suwartono, Tono (Educalitra: English Education, Linguistics, and Literature Journal, 2024)
Intercultural communicative competence stands as a cornerstone in modern English as a Foreign Language education, playing a pivotal role in nurturing learners' abilities to navigate diverse cultural landscapes. This systematic review meticulously examines the perspectives and practices of EFL educators in integrating intercultural communicative competence into language teaching, drawing insights from a comprehensive analysis of diverse studies across global contexts, the systematic review methodology of Gough and Newman’s way employed. The findings underscore a discrepancy between teachers' positive perceptions and practices in integrating intercultural communicative competence into the EFL classroom. Besides, the researchers highlight the responsibility of educators in fostering inclusive learning environments that empower learners with the indispensable skills for successful cross-cultural communication in an interconnected world.